Handicapping in squash. (17th November 2017) - Wagaman, John; Fletcher, Michael
Summary: This article considers how a handicapping system should be devised for squash. It looks at the American scoring system, and whether it is possible to have a fair system of handicapping. We consider 'fair' from a perspective of expected number of rallies won and probability of winning.